SIW Multibeam Array for 5G Mobile Devices - Qing-Ling Yang; Yong-Ling Ban; Kai Kang; Chow-Yen-Desmond Sim; Gang Wu (IEEE Access)
This paper presents a substrate integrated waveguide (SIW) multibeam slot array operating at $\sim 30$ GHz for future 5G mobile terminal applications. The multibeam forming network is realized with a Butler matrix that is composed of hybrid couplers, crossovers, and phase shifters (135° and 0°). The crossovers are formed with two cascaded hybrid couplers. In the design of 135° and 0° phase shifters, the phase compensation technique is employed. The slot array is a $2 × 4$ type, in which each column has two slot elements that are longitudinally staggered with respect to one another (in half-wavelength). In addition, mutual couplings reduction techniques applied in the proposed slot array are also discussed. The SIW technique is adopted in case for the related components, as it can be highly integrated in mmWave circuits at low fabrication cost and has low profile characteristics. The overall dimension of the SIW multibeam slot array (including the Butler matrix feeding network) is $72 × 27.4 × 0.508$ mm3, and the total area of the slot array is only $10.1× 20.4$ mm2. The measured 10 dB bandwidth was 28–32 GHz, and the measured gains at 30 GHz for each port were 10.8, 12.1, 12, and 11 dBi. The proposed slot array also possesses wide angle coverage of $\sim 40^{° }$ with good steerable radiation.